IMPLEMENTASI SISTEM MANAJEMEN MUTU ISO 9001:2008 PADA SMK NEGERI 2 BANDA ACEH - Ansaruddin .; Nasir Usman; Niswanto . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The purpose of this study was to find out the planning, implementation, supervision, and constraints found in the implementation of ISO 9001: 2008 quality management system (QMS) at State Vocational High School (SMK Negeri) 2 of Banda Aceh. The results of the study showed that: (1) QMS planning was begun by establishing a commitment of all school members and the core team, then building QMS in the form of quality awareness training, required QMS document preparation, and socialization; (2) the implementation of the QMS was done by applying the QMS document to the business process consisting of the planning, core, supporting, and improvement process of all units; (3) internal QMS supervision was done directly by the principal by involving all team leaders and through management meetings by discussing the results of internal audit. Meanwhile, external QMS supervision was conducted by the assessors of PT. TUV Rheinland Indonesia once a year. (4) The constraints found in the QMS were shortages of personnel, excessive personnel workload, rotation or mutation, inadequate facility in the form of equipment and required machinery, the budget allocated by the government each year, and business and industry (DU/DI) facilities in Banda Aceh City.Keywords: ISO 9001:2008, quality, management, system, QMS